Hình thái Tăng trưởng của các Địa phương Vùng Đông Nam Bộ - Lý Đại, Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The paper employs a quantitative analysis method with a panel dataset covering 63 provinces over the 2010-2021 period to focus on 6 provinces in South East region of Vietnam. The economic growth pattern of South East region still follows the common pattern of the whole economy, as a higher initial income combined with a lower income growth rate. In comparison with other provinces, the South East provinces is more affected by the labor force and institutional quality. The South East provinces are also leading the income growth convergence across provinces in the whole economy. In particular, Ho Chi Minh City is the leading province, expanding the income frontier for the other provinces. However, its income growth rate tends to decrease over time due to the reduction of the labor force, effective FDI capital, and institution quality.